Analisis Kesehatan Lingkungan Tebet Eco Park untuk Meningkatkan Kualitas Hidup Masyarakat (International Forum of Researchers and Lecturers, 2025)
Environmental health is very important for individual and community life. A healthy environment can improve the quality of life of the community to be better. Rapid community growth is one of the evaluations for the government to be able to create a healthy environment in the middle of a city filled with air, water, and soil pollution. The government's efforts to overcome environmental damage are to create green open spaces, one of which is Tebet Eco Park. This study aims to analyze the condition of cleanliness and environmental management in Tebet Eco Park towards environmental health in improving the quality of life of the community. Qualitative methods are used through in-depth interviews with various related parties. The analysis focuses on the condition of cleanliness and environmental management towards air, water, and soil quality; capacity and hygiene of sanitation facilities; and waste management. The results of the study are expected to provide recommendations to improve the environmental health of Tebet Eco Park and the quality of life of the community, including visitor management strategies, improving sanitation facilities, and environmental education programs.